The Effect of Brand Image and Customer Satisfaction on Manasta Customer Loyalty - Anwar, Syifa Zakiyah; Mubarok, Teten Mohammad Sapril; Herlianti, Anggun Oktavia (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
This study aims to determine and analyze the effect of brand image and customer satisfaction on Manasta Catering customer loyalty. Data was collected using q questionnaire distribution techniques using a Likert scale. the population in this study was obtained from manasta catering customer data in 2023, namely 400 customers. the sample was selected using the simple random sampling method and obtained a sample of 80 respondents using the Slovin formula. In this study using the classic assumption test, multiple linear analysis, and hypothesis testing. The hypothesis testing consists of the t test, f test and the coefficient of determination. The results stated that the brand image variable has an influence on customer loyalty of 58.7%, and the customer satisfaction variable has a significant value on customer loyalty of 41.2%. This means that the relationship between brand image and satisfaction with customer loyalty is 55.8%, which means that the hypothesis is accepted.